2023
DOI: 10.1039/d3gc02695g
|View full text |Cite
|
Sign up to set email alerts
|

Core–shell construction of metal@carbon by mechanochemically recycling plastic wastes: towards an efficient oxygen evolution reaction

Jiahua Zhao,
Qiang Niu,
Junjun Zhang
et al.

Abstract: Rational surface engineering of non-noble metal electrocatalysts supported on carbon materials (metal@C) provides potential opportunities to gain sustainable energy by electrocatalytic water splitting. Here, the plastic wastes-based electrode materials by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 116 publications
0
6
0
Order By: Relevance
“…Moreover, the thickness of the carbon layer has been confirmed to affect OER activity at both LCD and HCD strongly. Therefore, in addition to assessing the currently used mechanochemically assisted synthesis methods [124] or selecting appropriate types of metal-organic salts [125], future work could focus on developing other facile methods for controlling the thickness of the carbon layer. Convenient methods should also be developed to improve the stability of carbon-based electrocatalysts and avoid degradation [128].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the thickness of the carbon layer has been confirmed to affect OER activity at both LCD and HCD strongly. Therefore, in addition to assessing the currently used mechanochemically assisted synthesis methods [124] or selecting appropriate types of metal-organic salts [125], future work could focus on developing other facile methods for controlling the thickness of the carbon layer. Convenient methods should also be developed to improve the stability of carbon-based electrocatalysts and avoid degradation [128].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results demonstrate that an Fe/Fe 3 C-A@CNT sample with a surface carbon layer of ~1.77 nm thickness exhibits a lower overpotential (η 10 = 292 mV) and a smaller Tafel slope (29 mV dec −1 ) than samples with thicker carbon layers (>9 nm) (Fe/Fe 3 C-P@CNT and FeACAO@CT) and samples without a carbon layer (Fe/Fe 3 C-C@CNT) [125]. In another work, Zhao et al [124] found that the length of ball milling treatment (Figure 8d-f,h,i) also affected the thickness of the carbon shell when they employed a mechanochemical approach with plastic waste as the precursors to synthesize Ni@C electrocatalysts with tunable core-shell structures, octahedral-like crystal (OLC) morphology, and abundant surface defects. The ball milling process effectively facilitates the uniform dispersion of the metal precursor within the plastic matrix, resulting in an adjustable active core-shell structure.…”
Section: At Lcdmentioning
confidence: 95%
See 2 more Smart Citations
“…7 However, the scarcity of raw materials severely limits the large-scale application and commercial production. 8,9 Therefore, the preparation of low-cost, efficient, and stable non-precious metal-based nanocatalysts is a key strategy to improve the OER and promote water electrolysis. 10,11…”
Section: Introductionmentioning
confidence: 99%